Endoscopic tympanoplasty in subtotal perforations: conventional versus circumferential subannular grafting technique - Varghese, Bindu Sara; Narayanan, Nivee (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Tympanoplasty is a surgical procedure to reconstruct hearing mechanism impaired by chronic ear disease. Endoscopic technique has advantage of being minimally invasive, having better surgical view of the field, lesser postoperative pain and shorter duration of surgery. The aim of this study was to compare surgical outcomes of two techniques of endoscopic tympanoplasty in subtotal perforations. Methods: This prospective, comparative study was carried out between October 2016 to October 2018, in the Department of ENT, KMCT Medical College. 40 patients were randomly allocated to 2 groups of 20 each, to avoid selection bias and sample size calculated using the sample size formula. Group A underwent endoscopic tympanoplasty by conventional technique and Group B by circumferential subannular graft technique. Results: Post-operative evaluation of the patients for graft status showed 75% had successful graft uptake in Group A and 95% in Group B both groups had comparable, significant hearing improvement post operatively. Conclusions: Our study showed that, in all cases of subtotal perforations, the circumferential sub annular graft technique yielded a superior result with regards to the graft uptake compared to the conventional technique. The closure of the mean air-bone gap were significant, and similar among both the groups.